2008
DOI: 10.2188/jea.je2008012
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Countries---the United States and Japan: Are Differences in Health Due to Differences in Overweight?

Abstract: BackgroundDespite similar standards of living and health care systems for older persons, there are marked differences in the relative health of the elderly populations in the United States (US) and Japan. We explore the association of overweight and obesity with these health disparities.MethodsData on older adults from the US National Health Interview Survey (1994) and the Longitudinal Study of Aging II (1994) were compared to similar data from the 1999-2001 Nihon University Japanese Longitudinal Study of Agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 56 publications
1
34
2
Order By: Relevance
“…In the present study, which was limited to an apparently healthy population, body weight and body fat were significantly greater in U.S. than Japanese adults, although higher body weight or BMI is not always associated with greater mortality in either country, and most countries are experiencing increases in the prevalence of obesity . One of the few studies to address cross‐national differences between Japan and the United States noted that the prevalence of heart disease and diabetes mellitus was higher in the United States than in Japan but that the differences were rather small. Consistent with this, the current study found that the differences in BMI between the two samples were small and that adjusting for BMI did not affect the overall findings on intercountry differences in arterial stiffness.…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, which was limited to an apparently healthy population, body weight and body fat were significantly greater in U.S. than Japanese adults, although higher body weight or BMI is not always associated with greater mortality in either country, and most countries are experiencing increases in the prevalence of obesity . One of the few studies to address cross‐national differences between Japan and the United States noted that the prevalence of heart disease and diabetes mellitus was higher in the United States than in Japan but that the differences were rather small. Consistent with this, the current study found that the differences in BMI between the two samples were small and that adjusting for BMI did not affect the overall findings on intercountry differences in arterial stiffness.…”
Section: Discussioncontrasting
confidence: 55%
“…Briefly, within these study populations, the sample sizes ranged from 763 (19) to 69,492 (20), baseline measurements were collected prior to the year 2000 in all but one cross‐sectional study population (20), and all study populations except for one longitudinal (10) reported mean age or age ranges over 65 years old, or did not report mean age at all. All study populations were Caucasian, with the exception of a Japanese (21) and Puerto Rican Hispanic (9) population. BMI was self‐reported in 10 study populations and measured in 7.…”
Section: Resultsmentioning
confidence: 99%
“…While we recognize that the clinical significance of particular thresholds may differ across countries (e.g., with respect to weight: Ito et al 2003; Reynolds et al 2008; WHO Expert Consultation 2004), we use the same cutpoints for all markers in the two countries. We also examine treatment for hypertension and elevated cholesterol.…”
Section: Methodsmentioning
confidence: 99%